Tri Jati Diri sebagai Pilar Pendidikan : Menerapkan Kebudayaan Jawa Barat di Sekolah Dasar - Nurlela, Ayi; Ramadhan, Galih (Jurnal Ilmu Pendidikan Muhammadiyah Kramat Jati, 2025)
This study addresses the implementation of Tri Jati Diri in education, particularly in Civic Education (PKN) learning at elementary schools in West Java. The methodology employed is a literature review to gather and analyze relevant sources, including documents, articles, and previous research. The results indicate that the values of Silih Asah, Silih Asuh, and Silih Asih can be effectively integrated into the curriculum, aiming to shape students’ strong character and love for local culture. The study also identifies challenges such as a lack of resources and resistance to change among teachers. Practical recommendations are provided to support the implementation of these values in school environments. These findings are expected to serve as a guide for educators and policymakers in enhancing character education quality.